HEAVY METAL ADSORPTION ON MONTMORILLONITE AS A MODIFIER TO CARBON PASTE ELECTRODES - BAYRAM OVEZOV, BAYRAM (Universiti Teknologi Petronas, 2010)
Heavy metal pollutants in water samples cause severe health risks. A real-time, monitoring system is needed for instantaneous analysis of samples. Presently, CPEs represent one of the most frequent types of working electrodes. Carbon paste electrodes (CPEs) belong to promising electrochemical or bioelectrochemical sensors of wide applicability. Carbon paste electrodes have a wide range of anodic and cathodic utility and are inexpensive and easy to prepare and replace. These electrodes also have several drawbacks, such as a high cathodic residual current, a low resistance towards mechanical damage and electrochemical polymerization of analytes. Carbon Paste Electrodes can be modified simply to obtain quantitatively new sensors with desired, often predefined, properties. Electrode surfaces modified with clay offer the advantages of high chemical stability, known structural features and low cost. The electrochemistry of clay modified electrodes is a subject of considerable interest; recently, clay-modified electrodes have been used for studying transport in layered materials. Clays are able to adsorb an electroactive species for its direct determination. Objective of this project is to use clay as a modifier for carbon paste electrode and observe its performance after modification. The clay that will be used during project progress is Montmorillonite (MMT) because of its high cation exchange capacity and that its current market price is considered to be 20 times cheaper than that of activated carbon. Project is consists of 2 stages: preparation of Na-MMT and Anodic Stripping Voltammetry analysis. First stage is done in order to obtain monoionic MMT with same properties in all structure of clay. Second stage is done to observe performance of clay modified carbon paste electrode in which Na-MMT obtained from first stage will be used as clay.